2022
DOI: 10.5021/ad.21.223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capsaicin on Neuroinflammatory Mediators of Rosacea

Abstract: Background Rosacea is a chronic inflammatory skin disease with a pathophysiological mechanism that remains unclear. Recently, dysregulation of the sensory nerve system has been implicated in the development of this condition. Objective This study aimed to investigate the effect of capsaicin on neuroinflammatory mediators in rosacea. In addition, this study aimed to evaluate the attenuating effects of capsazepine, a transient receptor potential vanilloid type 1 (TRPV1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…CXCL8 expression in KCs is thought to be a key event in neutrophil recruitment for pustule formation; CRH activates the cannabinoid and vanilloid pathways, advancing the disease progression of rosacea. 43 , 44 …”
Section: The Hpa Axis In Endocrine Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…CXCL8 expression in KCs is thought to be a key event in neutrophil recruitment for pustule formation; CRH activates the cannabinoid and vanilloid pathways, advancing the disease progression of rosacea. 43 , 44 …”
Section: The Hpa Axis In Endocrine Factorsmentioning
confidence: 99%
“…The first wave of chemokines is subsequently produced, resulting in concentrated aggregation of T cells into the surrounding hair follicle space. 44 Conversely, T cell-derived cytokines, such as IL-17 or IL-22, may, together with UV radiation, activate KCs to produce CCL20, CXCL1, and CXCL8. CCL20 attracts additional Th17, while CXCL1 and CXCL8 absorb large numbers of neutrophils, leading to the formation of pustules.…”
Section: Th1/th17 Cell Polarization In Immune Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,17 Tumour necrosis factor Six studies reported on TNF-α, with all studies noting an increase. 11,17,19,20,23,24 T A B L E 1 T h 1 biomarkers in patients with rosacea.…”
Section: Interleukinsmentioning
confidence: 99%